2004
DOI: 10.1785/0120020219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Moderate-Size Earthquakes in Southern California Using Seismology and InSAR

Abstract: Source parameters determined from interferometric synthetic aperture radar (InSAR) measurements and from seismic data are compared from four moderate size (less than M 6) earthquakes in southern California. The purpose is to verify approximate detection capabilities of InSAR, assess differences in the results, and to test how the two results can be reconciled. First, we calculate the expected surface deformation from all earthquakes greater than magnitude 4 in areas with available InSAR data. A search for defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…The minimum threshold for the earthquake search was chosen based on the lowest limit of the coseismic detection capabilities of the DInSAR technique (EARLE and COGBILL 2002;MELLORS et al 2004;LOHMAN and SIMONS 2005;DAWSON and TRE-GONING 2007;DAWSON et al 2008). There are no studies about the sensitivity of DInSAR for detection and characterization of small and moderate sized events in the studied area.…”
Section: Seismicity During the Analyzed Periodmentioning
confidence: 99%
“…The minimum threshold for the earthquake search was chosen based on the lowest limit of the coseismic detection capabilities of the DInSAR technique (EARLE and COGBILL 2002;MELLORS et al 2004;LOHMAN and SIMONS 2005;DAWSON and TRE-GONING 2007;DAWSON et al 2008). There are no studies about the sensitivity of DInSAR for detection and characterization of small and moderate sized events in the studied area.…”
Section: Seismicity During the Analyzed Periodmentioning
confidence: 99%
“…For large earthquakes, InSAR has proved to be an important tool for source parameter estimation (Bürgmann et al 2000; Dawson & Tregoning 2007; Pritchard & Fielding 2008; Biggs et al 2009a and references therein). This method is independent of the seismic inversion and does not suffer from uncertainties associated with inadequate station coverage and is relatively independent of velocity models (Mellors et al 2004). However, InSAR cannot differentiate between distinct episodes of ground deformation that occur close together in space or between satellite acquisitions.…”
Section: Geodesymentioning
confidence: 99%
“…The location of the 1992 Little Skull Mountain earthquake (M s 5.4) in Nevada, reported by the Global Centroid Moment Tensor Project, was off by ∼42 km from that obtained by InSAR (Lohman et al, 2002). Mellors et al (2004) reported that it is difficult to accurately determine the source parameters of moderate-size earthquakes (4 < M < 6) in seismology, especially their epicentral location and focal depth. By systematically comparing earthquake source models derived from InSAR and those from seismic data, Weston et al (2012) found that InSAR provides more accurate location information for shallow events than do seismic catalogs.…”
Section: Introductionmentioning
confidence: 97%